2018
DOI: 10.3390/v10090457
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effect of Resveratrol in Piglets Infected with Virulent Pseudorabies Virus

Abstract: Pseudorabies virus (PRV) is one of the most important pathogens of swine, resulting in devastating disease and economic losses worldwide. Nevertheless, there are currently no antiviral drugs available for PRV infection. Resveratrol (Res) was identified to exert its antiviral activity by inhibiting the PRV replication in preliminary investigations. In our previous study, we found that Res has anti-PRV activity in vitro. Here, we show that Res can effectively reduce the mortality and increase the growth performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 34 publications
4
40
0
1
Order By: Relevance
“…Resveratrol is a natural compound and antioxidant found in peanuts, soy, hop, and various fruits, especially grapes and red wines [27, 28]. Resveratrol possesses various biological activities, including anti-tumour, anti-viral, anti-inflammation, anti-fungal, and antibacterial effects [27, 29-32]. We have demonstrated that resveratrol increases the expression of activating receptors on NK cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol is a natural compound and antioxidant found in peanuts, soy, hop, and various fruits, especially grapes and red wines [27, 28]. Resveratrol possesses various biological activities, including anti-tumour, anti-viral, anti-inflammation, anti-fungal, and antibacterial effects [27, 29-32]. We have demonstrated that resveratrol increases the expression of activating receptors on NK cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudorabies virus is one of the devastating pathogen of swine for which there is no treatment and that often result in economic losses. Resveratrol showed antiviral activity by inhibiting the Pseudorabies virus replication and effectively increase the growth performance and reduce the mortality of Pseudorabies virus-infected piglets [ 108 ].…”
Section: Biological Activities Of Resveratrolmentioning
confidence: 99%
“…3). In the antiviral effects of resveratrol in piglets infected with PRV, resveratrol can signi cantly inhibit the virus titer in the brain, and the levels of viral copies in the brain were positively linked to the clinical parameters of infected piglets [44]. Kaempferol were found effective to delay and inhibit the clinical symptoms in the PRVinfected mice which may attributed to inhibition of virus replication in the brain.…”
Section: Discussionmentioning
confidence: 93%
“…PRV (Ra strain) were preserved in the Natural Medicine Research Center Sichuan Agricultural University (Chengdu, China) [44], and the 50% tissue culture infective dose (TCID 50 ) was determined as 10 − 7.43 /mL. The virus was diluted to 1 × 10 4 TCID 50 with PBS before use.…”
Section: Virus and Chemicalsmentioning
confidence: 99%